Система ультразвукового локального позиционирования движущихся объектов - Ливнов, В. А. (ХНУРЭ, 2012)
The local position detecting system with high resolution based on ultrasound waves is analyzed. Structure scheme is designed and applied of the system for control of sportsmen is discussed